Europe in a new world order - Maria Demertzis; André Sapir; Guntram B. Wolff (Wirtschaftsdienst, 2018)
The EU is a relatively open economy and has benefited from the global multilateral system. We argue that the EU should defend its strategic interests with three steps. First, it should collaborate with partners around the world in defence of multilateralism. Second, it should establish deeper economic relations with emerging economies. Collaboration in support of the Paris agreement is also essential. Third, the EU must be reformed to increase its external credibility. The Singapore ruling has offered a useful clarification on trade policy. Addressing internal imbalances would also increase external credibility. Finally, strengthening Europe's social model would provide a counter model to protectionist temptations.
Keywords: F02; F13; F53; 330